The last Don - Puzo, Mario (London : Arrow Books, 1997)
In a corrupt world where crooked cops and desperate gamblers play dangerous games of betrayal, one man has power over them all The Last Don is Mario Puzo at his finest - a masterful saga of the last great American crime family, the Clericuzios, and their powerful reach into Hollywood and Las Vegas.
Keywords: v; Italian Americans -- Fiction